Effects of orthodontic treatment with a fixed appliance on the caries experience of patients with high and low risk of caries - Muhammet Karadas; Kenan Cantekin; Mevlut Celikoglu (Elsevier, 2011)
Background/purpose: We tested the hypothesis that there are no differences between changes in the caries experience in a group of orthodontic patients at high and low risk for caries. Materials and methods: Data were obtained from clinical and radiographic examinations of 186 orthodontic patients being treated with a fixed appliance in both arches. Patients were divided into two groups based on their prebonding decayed, missing, and filled permanent teeth (DMFT) scores and caries risk susceptibility. Statistical analyses were performed using the Wilcoxon and Mann-Whitney U tests. Results: Changes in DMFT values were 0.39 ± 0.66 and 1.46 ± 1.24 for the low- and high-caries risk groups, respectively. Changes in each group were significant (P < 0.001). Differences in DMFT scores between groups were also significant (P < 0.001). Additionally, males were found to have higher DMFT values than females. This difference was significant for the low-risk group (P < 0.001), but was not significant for the high-risk group (P > 0.05). Conclusion: The hypothesis was rejected; the difference in DMFT scores between the caries risk groups was statistically significant. Although patients in both groups cared for their teeth during treatment, oral hygiene after treatment was worse than that before treatment. These results suggest that conventional oral hygiene procedures, especially for patients in the high-caries risk group, are less useful in preventing carious lesions during orthodontic treatment, and thus such patients must follow a very rigid oral hygiene protocol during orthodontic treatment with a fixed appliance.